Review Literatur : Efektivitas Tumbuhan yang Mengandung Senyawa Flavonoid sebagai Antioksidan yang Berpotensi sebagai Hepatoprotektor - Karlina, Asta (Biocaster : Jurnal Kajian Biologi, 2023)
The liver plays an important role in maintaining the homeostasis of an organism, if there is damage to the liver it will disrupt its function and be fatal. Liver damage caused by poisons, drugs, and all other possible causes can be protected by compounds containing flavonoids as antioxidants which have the potential to become hepatoprotectors. The purpose of this literature review is to discuss the antioxidant effectiveness of several plants that have the potential as hepatoprotectors. The method used in this review is based on literature studies from several scientific publications in national journals on the effectiveness of plants containing flavonoid compounds as antioxidants used for hepatoprotectors, which consists of 16 articles. The results used from several studies show the effectiveness of the plant with each dose that has been tested.